Effects of Standardized Total Tract Digestible Phosphorus on Growth Performance, Carcass Characteristics, Bone Mineralization, and Economics of 53- to 287-lb Pigs - C. M. Vier; F. Wu; M. B. Menegat; H. S. Cemin; S. S. Dritz; M. D. Tokach; M. A. Goncalves; U. A. Orlando; J. C. Woodworth; R. D. Goodband; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 1,130 barrows and gilts (PIC; 359 × Camborough, initial pen average BW of 53.2 ± 1.61 lb) were used in a 111-d growth trial to determine the standardized total tract digestible (STTD) P requirement of growing-finishing pigs from 53 to 287 lb. Pens of pigs were randomly assigned to 1 of 6 dietary treatments in a randomized complete block design with BW as a blocking factor. There were 7 replicate pens per treatment and 26 to 27 pigs per pen (at least 13 barrows and gilts per pen). The experimental diets were corn-soybean meal-based and were fed in 4 phases. The 6 dietary treatments were formulated to contain 80, 90, 100, 115, 130, and 150% of the NRC publication STTD P requirement for growing-finishing pigs within each phase. The STTD P levels were achieved by increasing the amount of limestone and monocalcium phosphate at the expense of corn, maintaining a similar 1.14 to 1.16:1 total Ca:P ratio across treatments, with no added phytase. Overall, increasing STTD P resulted in a quadratic response in ADG, F/G, and final BW (P<0.05). The greatest improvement was observed with STTD P at 130% of NRC for ADG and final BW and 115% STTD P of the NRC recommendation for F/G. Average daily feed intake increased linearly with the inclusion of STTD P (P<0.05). Increasing STTD P resulted in a linear increase in fat-free bone ash weight and percentage ash (P<0.05). Barrows had significantly higher percentage ash compared to gilts (P<0.05). Increasing STTD P resulted in an increase in HCW and carcass ADG, with the greatest response observed with STTD P at 130% of NRC (quadratic, P<0.05). There was a marginally significant quadratic response in carcass F/G, with the greatest improvement with STTD P at 115% of NRC (P<0.10). Carcass yield decreased with increasing STTD P (linear, P<0.05), while there was a marginally significant decrease in backfat and increase in fat-free lean (linear, P<0.10). No difference was observed for loin depth (P>0.05). Feed cost per pig increased linearly with increasing STTD (P<0.05). Contrarily, gain value per pig and IOFC increased quadratically, with the greatest profit observed with STTD P at 130% of NRC (P<0.05). For ADG and feed efficiency, the quadratic model demonstrated the best fit. The maximum response in ADG was estimated at 122% of NRC STTD P, and the maximum response in feed efficiency was estimated at 116% of NRC STTD P. The broken-line linear model best fitted the data for ash as a percentage of fat-free dried bone, with a plateau achieved at 131% of the NRC STTD P requirement. In conclusion, the estimated STTD P requirement for growing-finishing pigs from 53 to 287 lb ranged from 116 to 131% of the NRC publication recommendations for each phase, depending on the response criteria and statistical model.
Keywords: phosphorus; finishing pigs; growth; bone mineralization